Pathology of Renal Diseases Associated with Dysfunction of the Alternative Pathway of Complement: C3 Glomerulopathy and Atypical Hemolytic Uremic Syndrome (aHUS) - Sethi, Sanjeev; Fervenza, Fernando C. (Seminars in Thrombosis and Hemostasis, 2014)
Dysfunction of the alternative pathway of complement in the fluid phase results in deposition of complement factors in the renal glomeruli. This results in glomerular injury and an ensuing proliferative response. The term “C3 glomerulopathy” is used to define such an entity. It includes both C3 glomerulonephritis and dense deposit disease (DDD). Both C3 glomerulonephritis and DDD are characterized by a proliferative glomerulonephritis and bright glomerular C3 mesangial and capillary wall staining with the absence or scant staining for immunoglobulins (Ig). The two conditions are distinguished based on electron microscopy findings: mesangial and capillary wall deposits are noted in C3 glomerulonephritis, while ribbon-shaped dense osmiophilic intramembranous and mesangial deposits are noted in DDD. On the contrary, uncontrolled activation of the alternative pathway of complement on endothelial cell surface results in endothelial injury with an ensuing thrombotic microangiopathy, termed atypical hemolytic uremic syndrome (aHUS). Kidney biopsy in aHUS is often indistinguishable from other forms of thrombotic microangiopathy including enterohemorrhagic Escherichia coli–induced HUS and thrombotic thrombocytopenic purpura and shows thrombi in glomerular capillaries, mesangiolysis, and endothelial injury as evidenced by swelling and double contour formation along the glomerular capillary walls, with negative immunofluorescence studies for Ig and complement factors and no deposits on electron microscopy.
Keywords: glomerulonephritis; classification; membranoproliferative glomerulonephritis; C3 glomerulonephritis; complement